Konseling Individual untuk Mengatasi Problematika Penyalahgunaan Narkoba pada Remaja - Ratu, Bau; Amelia, Laura; Azril, Moh.; Nur, Moh.; Putri, Putri; Nggego, Vitensia Meliani; Elfira, Ninil (Jurnal Wahana Konseling, 2024)
Adolescence is a transition stage from childhood to adulthood. In this phase, teenagers are very vulnerable to the influence of their peers' social environments. Lack of guidance and support from the immediate environment can encourage teenagers to dare to commit deviant acts to attract the attention of others. One form of juvenile delinquency that may occur is drug abuse. To face the challenges of drug abuse in adolescents, one approach that can be applied is individual counseling. This research uses a qualitative approach. The analytical method used in this research is the library research method. The analysis is carried out carefully, critically, and sharply so as to produce a synthesis that is logical and rational and can be tested. Through individual counseling sessions, teenagers can receive special guidance and support tailored to their unique needs and conditions in an effort to overcome drug dependence.